Art, self and knowledge - Lehrer, Keith (New York ; Oxford : Oxford University Press, 2011)
This text argues that a special value of art is the way in which it uses conscious experience - the exemplars of aesthetic experience - to autonomously reconfigure how we conceive of our world and ourselves, ourselves in our world and our world in ourselves.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Aesthetics; Art -- Philosophy; Representation (Philosophy); Experience